Chronic Blood Flow Restriction Exercise Improves Objective Physical Function: A Systematic Review - Clarkson, Matthew J.; May, Anthony K.; Warmington, Stuart A. (Frontiers in Physiology, 2019)
Background: Blood flow restriction or KAATSU exercise training is associated with greater muscle mass and strength increases than non-blood flow restriction equivalent exercise. Blood flow restriction exercise has been proposed as a possible alternative to more physically demanding exercise prescriptions (such as high-load/high-intensity resistance training) in a range of clinical and chronic disease populations. While the maintenance of muscle mass and size with reduced musculoskeletal tissue loading appeals in many of these physically impaired populations, there remains a disconnect between some of the desired clinical measures for chronic disease populations and those commonly measured in the literature examining blood flow restriction exercise. While strength does play a vital role in physical function, task-specific objective measures of physical function indicative of activities of daily living are often more clinically relevant and applicable for evaluating the success of medical and surgical interventions or monitoring age- and disease-related physical decline. Objective: To determine whether exercise interventions utilising blood flow restriction are able to improve objective measures of physical function indicative of activities of daily living. Methods: A systematic search of Medline, Embase, CINAHL, SPORTDiscus, and Springer identified 13 randomised control trials utilising an exercise intervention combined with blood flow restriction, while measuring at least one objective measure of physical function. Participants were ≥ 18 years of age. Systematic review of the literature and quality assessment of the included studies used the Cochrane Collaboration’s tool for assessing risk bias. Results: Data from 13 studies with a total of 332 participants showed blood flow restriction exercise, regardless of modality, most notably increased performance on the 30 second sit-to-stand and timed up and go tests, and generally improved physical function on other tests including walking tests, variations of sit-to-stand tests, and balance, jumping, and stepping tests. Conclusions: From the evidence available, blood flow restriction exercise of multiple modalities improved objective measures of physical function indicative of activities of daily living.